An interrogation of cognitive findings in pediatric obsessive–compulsive and related disorders. Issue 2 (30th June 2015) - Brennan, Elle; Flessner, Christopher
Abstract: Current findings in the field of psychology have led to increased interest and a new conceptualization of disorders characterized by repetitive behaviors, namely the obsessive compulsive and related disorders (OCRDs). Scant research, however, has sought to collect and categorize the extant research on pediatric OCRDs. Particularly, no adequate review of the pediatric cognitive literature existed until now, despite the clear implication of abnormalities in neuroanatomical structures and cognitive functioning in adult samples. While evidence for cognitive dysfunction in pediatric samples is presented, this paper also suggests that differences in cognitive dysfunction may indeed exist between adults and youth with OCRDs. Specifically, those irregularities present in said youth at varying developmental stages may impact the origination and maintenance of OCRDs across time. Finally, this paper seeks to formulate potential future goals for the research field, particularly through transdiagnostic approaches to processes linked with symptom presentations. This is of particular importance as an improved understanding of the interaction of cognitive function and growth is key to further comprehension of the OCRDs. Highlights: Neurocognitive deficits are characteristic of obsessive compulsive related disorders. Neurocognitive differences have been found between children and adults with OCD. Neurocognitive functioning and improvements may effect treatment response in OCRDs. Pediatric research focusing on developmental aspects of OCRDs is pointedly needed.